PEMANFAATAN LEARNING MANAGEMENT SYSTEM (LMS) DALAM PENGELOLAAN PEMBELAJARAN DARING PADA SATUAN PENDIDIKAN - I GUSTI NGURAH WIRAGUNAWAN (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2022)
The composition of the article on Utilization of Learning Management Systems (LMS) in Online Learning Management means to decide the adequacy of involving LMS in further developing understudy learning results during web based learning. The composition of this article is a writing concentrate on movement, to be specific by looking at different wellsprings of articles connected with the issues and destinations of the examination. The necessary information were gathered through printed investigations and afterward dissected utilizing content examination procedures. The utilization of LMS in learning makes it more straightforward for instructive foundations to further develop the learning system, gaining can be gotten to from different spots and limitless times, and learning can be completed all the more just. The utilization of LMS likewise makes learning more adaptable as far as study time and makes understudies more autonomous. Instructors can likewise screen understudy exercises through the LMS exhaustively. The outcomes got in light of the writing inspected include: (1) LMS is a media that is in extraordinary interest in web based realizing which is described by a significant degree of trust of 82.2% (2) LMS enjoys the benefit of complete elements contrasted with other internet based media so that learning happens more changed (3) Learning utilizing LMS or a mix of LMS-based learning models has been demonstrated to build the action, learning results, and inspiration of understudies in the "Upside" class (4) The utilization of LMS can make freedom in learning between the scope of 78.8 - 81.5 with exceptionally high classification. ABSTRAKPenulisan artikel Pemanfaatan Learning Management System (LMS) dalam Pengelolaan Pembelajaran Daring bertujuan untuk mengetahui efektivitas dari penggunaan LMS dalam meningkatkan hasil belajar peserta didik selama melaksanakan pembelajaran daring. Penulisan artikel ini merupakan kegiatan studi literatur yaitu dengan meneliti berbagai sumber artikel yang berhubungan dengan permasalahan dan tujuan dari penelitian.  Data yang dibutuhkan dikumpulkan melalui studi tekstual dan kemudian dianalisis menggunakan teknik analisis isi. Pemanfaatan LMS dalam pembelajaran memberi kemudahan bagi Lembaga Pendidikan dalam meningkatkan proses pembelajaran, pembelajaran dapat diakses dari berbagai tempat dan waktu yang tidak terbatas, serta pembelajaran dapat terlaksana dengan lebih sederhana. Penggunaan LMS juga membuat pembelajaran lebih fleksibel dari segi waktu belajar serta membuat peserta didik lebih mandiri. Guru juga dapat memantau aktivitas peserta didik melalui LMS secara detail. Hasil yang didapat berdasarkan literatur yang dikaji antara lain: (1) LMS merupakan media yang banyak diminati dalam pembelajaran daring yang ditandai oleh tingkat kepercayaan yang tinggi sebesar 82,2% (2) LMS memiliki kelebihan dari fitur – fiturnya yang lengkap dibanding media daring lainnya sehingga pembelajaran berlangsung lebih variatif (3) Pembelajaran menggunakan LMS maupun kombinasi model pembelajaran berbasis LMS telah terbukti dapat meningkatkan aktivitas, hasil belajar, serta motivasi peserta didik dengan kategori “Baik” (4) Penggunaan LMS dapat menciptakan kemandirian dalam belajar antara rentang 78,8 – 81,5 dengan kategori sangat tinggi.